Analysis of the Use of Indonesian as a Communication Tool for Product Marketing by Tiktokers - Ika Febriana; Nisa Artia Nababan; Rosana Vanessa Girsang; Silvia Putriani Silitonga; Stephen Malau; Tamara Meilita Marpaung (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research analyzes the use of Indonesian language by TikTokers as a product marketing communication tool on the TikTok platform. In the digital era, social media such as TikTok has become an effective means to reach a wide audience through visual and narrative content. The casual and familiar use of Indonesian allows TikTokers to build emotional closeness with the audience, increase the effectiveness of messages, and influence purchasing decisions. Through a qualitative approach, this study explores TikTokers' communication strategies in conveying relevant and persuasive messages, with language adapted to the characteristics of the target audience. Research results show that Indonesian is not just a communication tool, but also a strategy that strengthens audience engagement, grows trust, and influences purchasing decisions, so that it is effective in increasing product marketing conversions on TikTok.